WORK POSTURE ANALYSIS USING APPROACH METHOD OF RAPID UPPER LIMB ASSESSMENT (RULA) AT FABRIC CUTTER WORKERS TO REDUCE MUSCULOSKELETAL DISORDERS (MSDS) (RANGGANESVI HOME INDUSTRY CASE STUDY) - Irmawati, Nur Ayu; Widhy Wahyani (Bajang Institute, 2024)
Home Industry Convection Bag